Two‐Part Phase 1 Multiple‐Ascending‐Dose Study to Evaluate the Safety, Tolerability, Pharmacodynamics, and Pharmacokinetics of TRV734 in Healthy Adults. Issue 1 (3rd September 2021) - Ramos, Kimberly A.; James, Ian E.; Skobieranda, Franck; Soergel, David G.; Ruff, Dennis; Fossler, Michael J.
Abstract: TRV734, an oral G‐protein biased ligand at the μ‐opioid receptor has demonstrated differentiated pharmacology in preclinical studies compared to unbiased ligands. First‐time‐in‐human data suggested that TRV734 was safe and well tolerated and caused effective pain relief after single doses of 150 to 250 mg. In this study, safety and tolerability of multiple ascending doses of TRV734, and single doses of TRV734 125 mg following various administration paradigms, in healthy subjects were evaluated. In both parts of the study, TRV734 was generally well tolerated with no serious adverse events. Pharmacokinetics of TRV734 were similar when TRV734 125 mg was administered following a high‐fat or standard meal. Compared to either of the fed conditions, maximum concentration and area under the plasma concentration–time curve did not change, and time to maximum concentration was 1.5 hours later when TRV734 125 mg was administered as 3 split portions over 120 minutes under fasted conditions. Split doses of TRV734 delayed time to peak decrease in pupil diameter. Following multiple‐dose administration of TRV734 60 to 175 mg every 6 hours, there was a trend of slightly less‐than‐dose proportional increase of maximum concentration, and area under the plasma concentration–time curve and accumulation was modest. Time to maximum concentration was ≈1 to 2 hours and elimination half‐life ≈1.9 to 2.5 hours. The analgesic effect of TRV734 on the cold pain test was generally dose proportional and similar to that of oxycodone 10 mg immediate release, after both the first and last doses. There was a dose‐related decrease in pupil diameter following administration of TRV734 up to TRV734 125 mg every 6 hours. A favorable trend in bowel function index for TRV734 warrants continued study.